Pengaruh Kawin Sodor (Force Mating) Terhadap Persentase Kebuntingan Kelinci New Zealand White - Bayu Dewantoro P. Soewandi; T Kostaman; S. Sopiyana; T. Haryati (Jurnal Riset Agribisnis dan Peternakan, 2020)
Rabbits have the potential to produce meat for the animal protein consumption. At present, rabbit farming has developed in Indonesia.The development of rabbit farming is also Rabbits have the potential to produce meat for the animal protein consumption. At present, rabbit farming has developed in Indonesia.The development of rabbit farming is also accompanied by problems in the rabbit productivity. The problem that occurs in rabbit breeders is the low productivity of rabbits. The aim of this research was to identify the effect of force mating to the percentage of pregnancy in New Zealand White (NZW) rabbits at Indonesia Research Institute of Animal Production (IRIAP). The material used in this research were 99 heads New Zealand White (NZW) rabbits in the rabbit station at the IRIAP. The treatment in this study is that the dam of NZW is mated in natural mating and force mating. Pregnancy percentage data were analyzed using T test. The results showed that the percentage of pregnancy between natural and force mating was significantly different (P <.05). The percentage of pregnancy with natural mating in rabbits is higher when compared to force mating, but force mating can to increase the high percentage of pregnancy. The conclusion of the study is that the pregnancy percentage for force mating is lower when compared to natural mating. However, force mating can increase the percentage of pregnancy to reach 74%. by problems in the rabbit productivity. The problem that occurs in rabbit breeders is the low productivity of rabbits. The aim of this research was to identify the effect of force mating to the percentage of pregnancy in New Zealand White (NZW) rabbits at Indonesia Research Institute of Animal Production (IRIAP). The material used in this research were 99 heads New Zealand White (NZW) rabbits in the rabbit station at the IRIAP. The treatment in this study is that the dam of NZW is mated in natural mating and force mating. Pregnancy percentage data were analyzed using T test. The results showed that the percentage of pregnancy between natural and force mating was significantly different (P <.05). The percentage of pregnancy with natural mating in rabbits is higher when compared to force mating, but force mating can to increase the high percentage of pregnancy. The conclusion of the study is that the pregnancy percentage for force mating is lower when compared to natural mating. However, force mating can increase the percentage of pregnancy to reach 74%.